ENGAGING THE VISUALLY IMPAIRED STUDENTS TO LITERACY THROUGH ADAPTED GAMES (Proceedings of International Conference on Special Education, 2017)
Learning a foreign language for the visually impaired children with learning disability can be a stressful task. In this case, there is a need to create a learning atmosphere that decreases anxiety and captures the interest of the students. This is where the importance of integrating games in our language lessons comes in. There have been scholars in the field of language who contended that games are beneficial for language learners. These contentions inspired me to use adapted games to teach reading to five visually impaired students with learning disability. These students can recite and write the English alphabet in Braille (for the Braille readers) and in large print (for the Low Vision student). However, they cannot decode the written words or blend the sound-spelling patterns. Another factor that needs to be addressed is their short attention span and poor retention ability. To teach English Phonics and at the same time address these problems, I adapted games to deliver the lessons. These adapted games are played using materials with large print and Braille to cater to the needs of both the large print readers and the Braille readers. Subjects like Math and Science were also integrated in the lesson depending on the concept of the game. At the end of the school year, these five visually impaired students with learning disability were able to read short sentences and words with blended letters. They were also able to write simple words by listening to dictation. The use of adapted games as the heart of implementing the lessons and recognizing the element of play as essential in learning advances the literacy of visually impaired students with learning disability. This paper does not only explore on the academic benefits of adapted games but also on the emotional and social benefits that the students gain out of their educational experiences through games.